A Cu2Se–Cu2O film electrodeposited on titanium foil as a highly active and stable electrocatalyst for the oxygen evolution reaction. Issue 39 (30th April 2018) - Chen, Hu; Gao, Yan; Ye, Lu; Yao, Yanan; Chen, Xuyang; Wei, Yu; Sun, Licheng
Abstract : Cu2 Se–Cu2 O/TF electrode prepared via a simple and fast cathodic electrodeposition method. The electrode achieved a catalytic current density of 10 mA cm −2 for the OER at relatively low overpotential of 465 mV in 0.2 M carbonate buffer (pH = 11.0) and displayed a high durability over 20 h. Abstract : Many nonprecious metal-selenide-based materials have been reported as electrocatalysts with high activity for the oxygen evolution reaction (OER). Herein, a hybrid catalyst film composed of Cu2 Se and Cu2 O nanoparticles directly grown on Ti foil (Cu2 Se–Cu2 O/TF) was prepared through a simple and fast cathodic electrodeposition method. Surprisingly, this electrode required a relatively low overpotential of 465 mV to achieve a catalytic current density of 10 mA cm −2 for the OER in 0.2 M carbonate buffer (pH = 11.0). Furthermore, a long-term constant current electrolysis test confirmed the high durability of the Cu2 Se–Cu2 O/TF anode at a current density of 10 mA cm −2 over 20 h. The XRD, TEM and XPS analysis of the sample after the OER indicated that a CuO protective layer formed on the surface of the Cu2 Se–Cu2 O catalyst, which effectively suppressed further oxidation of the Cu2 Se–Cu2 O catalyst during the OER and resulted in sustained catalytic oxidation of water.